Whey proteins processing and emergent derivatives: An insight perspective from constituents, bioactivities, functionalities to therapeutic applications. (December 2021) - Mehra, Rahul; Kumar, Harish; Kumar, Naveen; Ranvir, Suvartan; Jana, Atanu; Buttar, Harpal Singh; Telessy, Istvan G.; Awuchi, Chinaza Godswill; Okpala, Charles Odilichukwu R.; Korzeniowska, Małgorzata; Guiné, Raquel P.F.
Graphical abstract: Highlights: Whey is a potential resource for numerous value-added products. Whey-derived natural products and their usefulness in human health are summarised. Whey derived peptides display a wide range of physiological actions. Whey-derived products and their therapeutic applications, also discussed. Abstract: The massive research interest in whey has strengthened its position among coagulated milk products. Previously conducted reviews demonstrate that whey-derived functional foods provide a cascade of beneficial applications that promote health and wellbeing, and in managing numerous chronic diseases. To improve the understanding about how whey protein processing brings about new products that help in tackling health challenges is what we have attempted in this review paper. Herein, we provide an insight perspective into whey proteins processing and its derivatives from constituents, bioactivities, functionalities to therapeutic applications, drawing from: (a) prime constituents of whey protein; (b) composition and production of sweet/acidic whey; (c) bioactive peptides aspects of whey and its health/wellbeing benefits; (d) whey processing techniques: improving whey proteins' functionalities; (e) whey and its derivatives-based products: generating new functional foods and beverages and (f) whey-derived products in health and wellbeing: some therapeutic applications.